Factors Affecting Contingent Liabilities in the Public Sector - Motubatse, K. N.; Chauke, K. R. (Indian Journal of Finance, 2022)
Inappropriately accounted-for contingent liabilities could result in government departments having to make enormous payouts. The purpose of this study was to evaluate factors affecting contingent liabilities in the public sector, using the audited financial statements of four national government departments in South Africa as the data set. The four departments are Education, Correctional Services, South African Police Services, and Health. Data from 12 years, 2007/8 to 2018/19, for each department were analyzed. The paper applied a quantitative approach using positive accounting theory to explain accounting practices on the effects of litigation claims and intergovernmental payables on the departments’ contingent liabilities. In addition, a Spearman correlation analysis was used to evaluate factors affecting the contingent liabilities of litigation claims (LC) and interdepartmental payables (IP). The study results indicated a statistically significant positive relationship between litigation claims and interdepartmental payables. The results further confirmed that both variables significantly impacted the growth of contingent liabilities in the public sector. The benefit of this study is that determining the escalation and quantum of contingent liabilities may encourage government departments to implement policies that promote efficient management and accounting practices to contain and eventually reduce contingent liabilities accounts’ transactions. Achieving this will significantly reduce government departments’ unproductive cash outflows, measured in millions of rands annually.